2021
DOI: 10.3390/ijms22137073
|View full text |Cite
|
Sign up to set email alerts
|

Gene Variant of Barrier to Autointegration Factor 2 (Banf2w) Is Concordant with Female Determination in Cichlids

Abstract: Oreochromis fishes exhibit variability of sex-determination (SD) genes whose characterization contributes to understanding of the sex differentiation network, and to effective tilapia farming, which requires all-male culture. However, O. niloticus (On) amh is the only master-key regulator (MKR) of SD that has been mapped (XY/XX SD-system on LG23). In O. aureus (Oa), LG3 controls a WZ/ZZ SD-system that has recently been delimited to 9.2 Mbp, with an embedded interval rich with female-specific variation, harbori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
0
7
1
Order By: Relevance
“…hornorum and P . mariae with ZW sex determining system ( Curzon et al, 2021 ). However, the W-specific banf was not identified in the female fish of Family2 with ZW sex determining system based on the re-sequencing data, suggesting the existence of a different female sex determiner in O .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hornorum and P . mariae with ZW sex determining system ( Curzon et al, 2021 ). However, the W-specific banf was not identified in the female fish of Family2 with ZW sex determining system based on the re-sequencing data, suggesting the existence of a different female sex determiner in O .…”
Section: Discussionmentioning
confidence: 99%
“…hornorum and P . mariae ( Curzon et al, 2021 ). The major sex-determination gene on LG23 is a duplication of amh , which is known to play an important role in the vertebrate sex-determination network ( Li et al, 2015 ; Pan et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…However, different fish species have adopted different MKR genes to initiate the sex cascade, which determines the fate of the bipotential sex gonad [ 11 ]. During the last year, two new MKRs ( bmpr1b and banf2w ) have been suggested [ 12 , 13 ], in addition to ten SD MKRs detected previously [ 11 ]. In most cases in fishes, as in other vertebrates, Y and W differ from X and Z, respectively, in the number of copies and sequences [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, purebred species of tilapia possess monofactorial SD systems such as WZ/ZZ and XX/XY [ 30 , 31 ]. Nevertheless, On , Oa , and their hybrids have been reported to segregate for three SD loci on LGs 1 [ 32 , 33 ], 3 [ 12 , 34 ], and 23 [ 14 , 35 , 36 ]. Purebred Oa and On have been reported to segregate for the SD systems on LGs 3 (WZ/ZZ) and 23 (XX/XY), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic sex determination (GSD) systems have evolved independently and repeatedly, involving various master sex determining (MSD) genes [3,4]. In teleosts, almost all the identified MSD genes are members of gene families involved in gonad development, including DMRT1, members of the SOXA and B1 protein families and TGF-β signalling pathway as reviewed by Pan et al [5] or genes that interact with these pathways [6,7], except for a few exceptions [8,9]. A recent study in the fish genus Seriola revealed that a steroidogenic enzyme gene, hsd17b1 evolved to be an MSD gene, providing an exceptional case of the diversity of MSD genes [10].…”
Section: Introductionmentioning
confidence: 99%